Mental wandering and its relationship to the fluency of forms among students of Wasit University, College of Education for Human Sciences, as a model - عبد الكاظم حسين حازم (Journal of College of Education, 2021)
The mental wandering problem is one of the problems that will receive the attention of educational and psychological researchers due to its negative repercussions on many variables among students, such as problem-solving skills, reading comprehension skills, psychological and cognitive integration , cognitive burden and academic performance of students (El-Fil, 2018:211): University education is the top of the educational pyramid, which is entrusted with graduating active generations in all disciplines capable of competition. Education has a vital and effective role in making the lives of peoples and societies, (El-Fil, 2018: 75) making the lives of peoples and societies. (The Elephant, 2018: 75) The current research aims to know the level of mental wandering among students of Wasit University College Education for the Humanities, and the current research sample consisted of students of Wasit University, College of Education for Human Sciences, and in order to reach the results, the data was analyzed statistically, so the Statistical Program for Social Sciences (SPSS) was used and the research came out with results, including that the degree of mental wandering among university students as a whole was Not a moral function, and this means that the sample members do not have mental wandering. As for the most important research recommendations, it is to improve attention and develop attention for university students through training programs. As for the research proposals, it is to study research variables on other samples of middle school students.